Pendampingan Terpadu Remaja dan Lansia untuk Masyarakat Sejahtera Di RT19 Karang Indah Kelurahan Sumur Dewa Bengkulu - Fahimah, Iim; R, Siti Badria Ainur; Rosana, Gebby; Tahira, Meza (Pakis Journal Institute, 2025)
This research was conducted by students of KKN MBKM Group 1 Batch IV 2025, Fatmawati Sukarno Bengkulu State Islamic University with a focus on integrated assistance to elderly teenagers for a prosperous society. The aim is to determine the effectiveness of integrated assistance for elderly teenagers in improving community welfare in RT 19 Karang Indah, Sumur Dewa Village, Bengkulu City. This research method uses a participatory and collaborative approach between teenagers and the elderly in carrying out mentoring activities. The research results show that integrated assistance to elderly teenagers can improve community welfare by increasing the active participation of teenagers and elderly people in social and economic activities. This research also shows that cooperation between teenagers and the elderly can strengthen intergenerational relationships and increase public awareness about the importance of shared prosperity